2018
DOI: 10.1016/j.ophtha.2018.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Highly Asymmetric Keratoconus Eyes Using Combined Scheimpflug and Spectral-Domain OCT Analysis

Abstract: Individual machine-derived metrics from Scheimpflug and SD OCT imaging poorly distinguished normal eyes from minimally affected eyes from patients with highly AKC. Combined SD OCT metrics performed better than combined Scheimpflug metrics. Combining anterior curvature and asymmetry indices from Scheimpflug with regional total thickness and epithelial thickness variability metrics from SD OCT clearly distinguished the 2 populations. Posterior corneal indices were not useful in distinguishing populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
97
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 48 publications
4
97
0
3
Order By: Relevance
“…The classification was significantly better, when indices from both devices were used simultaneously . The logistic regression model produced a differential classification of asymmetric normal eyes since the model included thickness variables, had smaller sample sizes and lacked FFKC eyes compared to our study . However, a comparison of the Pentacam indices from the earlier and our study revealed similar magnitudes for the VAE‐NT eyes.…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations
“…The classification was significantly better, when indices from both devices were used simultaneously . The logistic regression model produced a differential classification of asymmetric normal eyes since the model included thickness variables, had smaller sample sizes and lacked FFKC eyes compared to our study . However, a comparison of the Pentacam indices from the earlier and our study revealed similar magnitudes for the VAE‐NT eyes.…”
Section: Discussionmentioning
confidence: 41%
“…The logistic regression model produced a differential classification of asymmetric normal eyes since the model included thickness variables, had smaller sample sizes and lacked FFKC eyes compared to our study . However, a comparison of the Pentacam indices from the earlier and our study revealed similar magnitudes for the VAE‐NT eyes. Thus, the earlier study supported our conclusion that the VAE‐NT eyes could have the same features as normal eyes topographically.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…AI has been applied to various adult ophthalmic diseases, including diabetic retinopathy [1,[74][75][76][77], AMD [78][79][80][81][82][83], sight-threatening retinal disease [2,[84][85][86][87][88][89], glaucoma [90][91][92], intraocular lens calculation [93], and keratoconus [94]. It has also been used for robotassisted repair of epiretinal membranes [95], retinal vessel segmentation [96][97][98][99], and systemic disease prediction from fundus images [100].…”
Section: Non-pediatric Applicationsmentioning
confidence: 99%